2018
DOI: 10.1088/1742-6596/1057/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Growth Temperature on The Characteristics Of ZnO Nanorods And Its Optical Properties

Abstract: The aim of this research is to identify the effects of growth temperature on the characteristics of ZnO nanorods synthesized by the hydrothermal method. The Zinc oxide (ZnO) nanorods synthesis was carried out through two steps, consisting of the ZnO seed layer deposition and the ZnO nanorods growth. The ZnO seed layer was prepared by a spin coating method using zinc acetate dehydrate and ethanol on ITO substrate. The following ZnO nanorods growth was performed with the modified hydrothermal method by using hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The band gap values exhibit a red shift relative to 3.37 eV of bulk ZnO related to the quantum confinement effect of the synthesized nanorods [ 55 ]. A similar trend was observed from other studies [ 66 ]. Contrary to our results, the band gap energy obtained from absorbance spectra increased as the temperature increased from 70 °C to 90 °C due to quantum confinement effect [ 67 ].…”
Section: Resultssupporting
confidence: 92%
“…The band gap values exhibit a red shift relative to 3.37 eV of bulk ZnO related to the quantum confinement effect of the synthesized nanorods [ 55 ]. A similar trend was observed from other studies [ 66 ]. Contrary to our results, the band gap energy obtained from absorbance spectra increased as the temperature increased from 70 °C to 90 °C due to quantum confinement effect [ 67 ].…”
Section: Resultssupporting
confidence: 92%
“…The average diameter of the ZnO/GO nanostructures grown at 95˚C GO solution immersion temperature has smallest value compared to other samples. The patterns of this results are similar with previous research and as reported that the increasing temperature of the solution produced adequate heat energy for the atom nucleation which improve the surface mobility to be more active [17]. This demonstrates that the GO solution immersion temperature has a significant influence on the size of ZnO/GO nanostructures.…”
Section: Morphology Resultssupporting
confidence: 90%
“…As reported by Liang et al, the active materials that has better crystallinity structure would give better dye absorption as well as faster electron injection in DSSC [16]. The full width half maximum (FWHM) value was used to calculate the average crystallite size using the Scherrer equation 1 [17].…”
Section: Structural Resultsmentioning
confidence: 99%
“…Additionally, Mufti et al found that the morphology and optical properties of ZnO nanorods synthesized from two different precursors using a simplified hydrothermal technique are mainly solution temperature dependent [24]. The aspect ratio (defined as the ratio of nanorods length to diameter) is one of the important variables that can affect the ZnO nanorod's performances.…”
Section: Introductionmentioning
confidence: 99%